Volunteer Missions for Digital Transformation: Educational Experiences - Eftimova, Sabina; Dimitrova, Svetoslava (Bobcatsss, 2023)
The European Union is focusing on digital transformation through various mechanisms. One of the new framework programs – Horizon Europe (2021-2027) with a budget of over 100 billion euros – aims to precisely support the digital transformation and, along with investment in supercomputers, artificial intelligence, and cybersecurity, will stimulate skills development. The digital transformation has opened new opportunities for access to information for people with special needs in Bulgaria. At the University of Library Studies and Information Technologies (ULSIT) – Bulgaria, at the Faculty of Library Studies and Cultural Heritage (FLSCH) for ten years, part of the curriculum is the elective course “Access to Information for People with Special Needs” (AIPSN). It is an opportunity to expand the skills of future professionals to work with a wide group of users. In recent years, there have been more and more occasions for reasoning volunteering as a social phenomenon and assessing its practical dimensions, starting with the motivation of volunteers, and reaching to all aspects of the benefits for society. An element of the training in the elective course “Access to Information for People with Special Needs” is the inclusion of students in various volunteer missions, that also contribute to the enrichment of information resources for people with visual difficulties. This happens thanks to the platform Bemyguide.org, created to help people with visual difficulties in the perception of various phenomena, objects, people, through text descriptions of photographs and videos. The goal of this paper is to reveal the possibilities for enriching the information resources for people with visual impairments in Bulgaria by involving students in the volunteer initiative of the Bemyguide.org platform. The current research is based on an analysis of the results of the learning process with undergraduate students in the period 2016-2020. The achievements of the students' activities as volunteers in the Bemyguide.org platform is statistically summarized and an overview of the issues and achievements of defended diploma theses on this topic. Conclusions are reached about the effectiveness and prospects of this pedagogical approach for fostering empathy and commitment of the future library and information professionals to the opportunities for enrichment of information resources for people with visual impairments in Bulgaria. The opportunities and benefits of volunteering for students are multifaceted. The new approaches for the inclusion of volunteering in the content of the elective course “AIPSN” contributes to the enrichment of traditional education in the specialties preparing library professionals in Bulgaria. This is a good practice that can be multiplied and to be of an interest for the international audience.